POLITIK DINASTI DI ACEH; STUDI KEPEMIMPINAN AMPON BANG DI KABUPATEN NAGAN RAYA - Ramadhan, Ilham; Aklima (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
The focus of study the political dinasti strategic Ampon Bang of Nagan Raya distric. The aim of reseach to find out the political strategic that strengthens the couse of the political dynasty Ampon Bang aplicatin in Nagan Raya distric.The methodology used is qualitatif methode collecting data throughdocumentation and in dept interview technic. The Result of the research obtained political dynasty leadershipAmpon Bang Usingthe concept of the families with the political strategic carried out; first, leadership organisation structure is filled by family and relatives. Second, close the space for public partisipation.